2000
DOI: 10.1097/00001756-200011090-00044
|View full text |Cite
|
Sign up to set email alerts
|

The dendritic architecture of prefrontal pyramidal neurons in schizophrenic patients

Abstract: Despite a considerable number of investigations revealing the prefrontal cortex (PFC) to be a major site of pathological changes in schizophrenia, the neuronal basis of these alterations is still unknown. We used a 3-D image analysis technique to investigate the dendritic arborization of Golgi-impregnated prefrontal pyramidal neurons in schizophrenic patients and controls. While the apical dendrites were found to be unchanged in schizophrenics, the basilar dendritic systems were markedly reduced in the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 13 publications
5
75
0
Order By: Relevance
“…34 In addition, loss of MAP2 was also reported in the medial prefrontal cortex (PFC) of patients with this same disorder. 35 A decrease in dendritic length was encountered by a 3D image analysis on the PFC of patients with schizophrenia 36 and similar results were evidenced in the hippocampus. 37 Reduced interneuronal space, decreased dendritic markers, smaller neuronal soma sizes and a reduction in dendritic length are all findings that support the 'reduced neuropil hypothesis'.…”
Section: Introductionsupporting
confidence: 66%
“…34 In addition, loss of MAP2 was also reported in the medial prefrontal cortex (PFC) of patients with this same disorder. 35 A decrease in dendritic length was encountered by a 3D image analysis on the PFC of patients with schizophrenia 36 and similar results were evidenced in the hippocampus. 37 Reduced interneuronal space, decreased dendritic markers, smaller neuronal soma sizes and a reduction in dendritic length are all findings that support the 'reduced neuropil hypothesis'.…”
Section: Introductionsupporting
confidence: 66%
“…Studies examining the dendritic morphology of Golgiimpregnated pyramidal neurons in the prefrontal cortex of schizophrenic patients and have found reductions in spine density, dendritic complexity, and dendritic length that are consistent with the postulated reduction in cortical communication (Garey et al, 1998;Glantz and Lewis, 2000;Kalus et al, 2000;Broadbelt et al, 2002;Black et al, 2004). In the AMPH-sensitized monkey, we observed a reduction in complexity of dendrites in layer II/IIIs and a reduction in dendritic length in pyramidal cells across all layers.…”
Section: Implications For the Neuropathology Of The Prefrontal Cortexsupporting
confidence: 83%
“…However, evidence linking disturbances in dopamine neurotransmission to structural pathology in the brain has been lacking. For example, post-mortem studies of the prefrontal cortex from patients with schizophrenia patients have described reductions in spine density, dendritic length, and complexity in the basilar dendrites of pyramidal cells in layers III and V (Garey et al, 1998;Glantz and Lewis, 2000;Kalus et al, 2000;Broadbelt et al, 2002;Black et al, 2004). However, it is not known whether there is a causal effect between the purported neurochemical imbalance in the dopaminergic innervation of the prefrontal cortex and the observed abnormalities in dendritic architecture of pyramidal cells in this region.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a recent study has demonstrated a strong correlation between the loss of asymmetric spine synapses in monkey PFC and cognitive impairment during aging (Peters et al, 2008). Several groups have reported dystrophic changes in frontal cortical pyramidal cell dendrites in schizophrenia, including decreases in dendritic length, branching, and spine density (Black et al, 2004;Broadbelt et al, 2002;Garey et al, 1998;Glantz and Lewis, 2000;Kalus et al, 2000;Kolluri et al, 2005), consistent with the hypothesis that these changes are involved in the cognitive dysfunction that typifies the disorder. It is not currently known though whether the pathological changes in the cortex in schizophrenia are fixed or can be altered by treatment with antipsychotic drugs.…”
Section: Introductionmentioning
confidence: 69%